1993
DOI: 10.1111/j.1600-0714.1993.tb01044.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of thermal trauma in experimental oral mucosal Candida infections in rats

Abstract: A model of candidosis in experimental rats was used to study the role of trauma in the aetiology of oral mucosal infections caused by Candida albicans. Standardised thermal trauma was delivered to the dorsum of the tongue of Sprague-Dawley rats and experimental candidosis was induced. Histologically, the site of trauma was invaded by hyphae earlier and more extensively than in control animals, leading to the conclusion that trauma facilitated the establishment of the C. albicans infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
2

Year Published

1994
1994
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 22 publications
0
17
0
2
Order By: Relevance
“…The authors therefore concluded that the hyposalivatory-rat model is useful to assess the infectivity, pathogenesis, and virulence of different Candida strains in both qualitative and quantitative terms. A relationship between Candida infection and mucosal trauma has been addressed by other workers (30,131,195). When the role of thermal trauma to the oral mucosa was investigated, it was noted that thermal ulceration facilitated candidal invasion of the dorsal lingual mucosa (131).…”
Section: Sprague-dawley Rat Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors therefore concluded that the hyposalivatory-rat model is useful to assess the infectivity, pathogenesis, and virulence of different Candida strains in both qualitative and quantitative terms. A relationship between Candida infection and mucosal trauma has been addressed by other workers (30,131,195). When the role of thermal trauma to the oral mucosa was investigated, it was noted that thermal ulceration facilitated candidal invasion of the dorsal lingual mucosa (131).…”
Section: Sprague-dawley Rat Modelmentioning
confidence: 99%
“…A relationship between Candida infection and mucosal trauma has been addressed by other workers (30,131,195). When the role of thermal trauma to the oral mucosa was investigated, it was noted that thermal ulceration facilitated candidal invasion of the dorsal lingual mucosa (131). These results also suggested that mild, long-term trauma due to chronic irritation from unstable dentures may contribute to the initiation or aggravation of Candida-associated denture stoma- titis.…”
Section: Sprague-dawley Rat Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The percentage of areas of clinical lesions was analyzed by Student's t test (25). The Wilcoxon signed-rank sum test for paired comparisons and the Kruskal-Wallis test for multiple comparisons were used to determine the degree of colonization of the epithelium by fungal hyphae (33). Differences were considered significant at P Ͻ 0.05.…”
Section: Methodsmentioning
confidence: 99%
“…Both hematoxylin and eosin and periodic acid-Schiff stains were used. C. albicans infection was assessed with a digital imaging system according to evidence of lesions and hyphal colonization on the dorsal tongue (3,33). Tissue injury was determined by quantification of the number and type (normal, atrophic, and hypertropic) of papillae per microscopic field (magnification, ϫ46).…”
Section: Methodsmentioning
confidence: 99%